2021
DOI: 10.1038/s41598-021-00586-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the seismic potential of the Indo-Burman megathrust

Abstract: The Indo-Burman arc is the boundary between the India and Burma plates, north of the Sumatra–Andaman subduction zone. The existence of active subduction in the Indo-Burman arc is a debatable issue because the Indian plate converges very obliquely beneath the Burma plate. Recent GPS measurements in Bangladesh, Myanmar, and northeast India indicate 13–17 mm/y of plate convergence along a shallow dipping megathrust while most of the strike-slip motion occurs on several steep faults, consistent with patterns of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The Indo-Burmese megathrust is associated with the Indo-Burma Subduction beneath the Indo-Burma range. The recent studies by Steckler et al (2016) and Vorobieva et al (2021) suggest that this mega thrust is locked and may produce a great earthquake (M > 8.0), which may affect the adjoining regions, including the study area (EH).…”
Section: Seismicity Landslides and Tectonic Setupmentioning
confidence: 99%
“…The Indo-Burmese megathrust is associated with the Indo-Burma Subduction beneath the Indo-Burma range. The recent studies by Steckler et al (2016) and Vorobieva et al (2021) suggest that this mega thrust is locked and may produce a great earthquake (M > 8.0), which may affect the adjoining regions, including the study area (EH).…”
Section: Seismicity Landslides and Tectonic Setupmentioning
confidence: 99%
“…Meanwhile, only models of type-III dealing with fault dynamics allow for simulating realistic earthquakes (Ismail-Zadeh et al, 2018). For example, several models were developed in the case of a large heterogeneous fault (e.g., Ben-Zion and Rice 1993;Lyakhovsky et al 2001;Zöller et al 2005;Lapusta and Liu 2009;Nodal and Lapusta 2010) and in the case of a system of faults (e.g., Gabrielov et al 1990Gabrielov et al , 2007Ward 1992Ward , 1996Ward , 2000Benites 1996, 2001;Panza et al 1997;Fitzenz and Miller 2001;Soloviev and Ismail-Zadeh 2003;Rundle et al 2006;Zhou et al 2006;, 2012aPeresan et al 2007;Zöller and Hainzl 2007;Pollitz 2009;Bielak et al 2010;Vorobieva et al 2014Vorobieva et al , 2019Vorobieva et al , 2021. The results of the modelling improved significantly our understanding of earthquake occurrences and seismic hazards.…”
Section: Models Of the Lithosphere Dynamics Stress Building And Earthquakesmentioning
confidence: 99%
“…The BAFD model was applied to study seismicity and statistics of earthquakes in several earthquake-prone areas, such as the south-eastern Carpathians (Panza et al 1997;Soloviev et al 1999;Ismail-Zadeh et al 1999), the central Alpine-Himalayan belt (Sobolev et al 1999), the western Alps (Vorobieva et al 2000;Soloviev and Ismail-Zadeh 2003), Sunda island arc (Soloviev and Ismail-Zadeh 2003), Tibet-Himalaya (Ismail-Zadeh et al 2007;Vorobieva et al 2017Vorobieva et al , 2021, Italy and its surroundings (Peresan et al 2007), Kachchh rift zone (Vorobieva et al 2014), and Caucasus (Soloviev and Gorshkov 2017;Vorobieva et al 2019). Here, we overview the application of the BAFD model to the orogenic regions, such as Carpathians, Caucasus, and Tibet-Himalaya, as well as to the Sunda arc, associated with the Indo-Australian plate subduction, which have been subjects to earlier surveys (Soloviev and Ismail-Zadeh 2003;Ismail-Zadeh et al 2012a, b;Ismail-Zadeh et al 2018).…”
Section: Bafd Model Applicationsmentioning
confidence: 99%
“…The block-and-fault dynamics modeling of the Himalayan frontal arc (Vorobieva et al 2017) has shown maximum earthquake hazard for the central Himalayan GAP area while minimum hazard has been modeled for the Bhutan Himalaya. Modeling the seismicity of the Indo-Burma arc has shown a high seismic potential in this region of India, where great M8 + earthquakes can occur (Vorobieva et al 2021).…”
Section: Seismicity and Earthquake Hazard Research In Gujaratmentioning
confidence: 99%